'A conflict between the token guardians of society and a man's private life': Kenneth Anger, Palo Alto Kodak, the Kinsey Institute, and the circulation of Marvin Samuel's amateur S/M pornography. Issue 4 (2nd October 2022) - Silvestri, Anthony L.
ABSTRACT: This article traces the route that a piece of amateur, gay S/M pornography took in the era before the golden age of pornography, looking at how it moved through the stages of production, development, processing, and viewing. In doing so, the article charts a history of pornography outside the confines of pleasure by examining the many significances that were ascribed to the films by distinct individuals and institutions like Kenneth Anger, Palo Alto Kodak, the Institute for Sex Research, and the judges of the California legal case. This, I argue, not only dramatizes several ethical concerns about S/M in a non-academic venue, but also cultivates a greater understanding of use-values historically attributed to pornography, while showing the stage of film development and processing to be crucial, if often overlooked, in the production of film.